Relationship Of Mileage Work And Family Support With a Complete Postnatal - Purwanti Purwanti; Siti Aisyah; Helni Anggraini; Fika Minata (Jurnal MID-Z (MIDWIFERI ZIGOT), 2022)
Globally, 289,000 women die from complications related to pregnancy, childbirth or the postnatal period each year. Postnatal care is essential to prevent complications during the puerperium. This study aims to determine the relationship between mileage, work and family support with complete postpartum visits at the Griya Sehat Clinic, East Ogan Komering Ulu (OKU) Regency in 2021. The method in this study used an analytical survey with a cross sectional approach. The population in this study were all mothers giving birth at the Griya Sehat Clinic in 2021 as many as 65 respondents and a sample of 65 respondents using the total sampling technique. Collecting data using primary data through interviews by distributing questionnaires. Data analysis used chi square statistical test with p value value (0.05). The results of this study were from 31 respondents who traveled close to a complete postpartum visit as many as 27 people (87.1%) with p value = 0.000, of 27 respondents who worked with a complete postpartum visit as many as 14 people (51.9%) p value = 1,000, meanwhile, from 41 respondents who received family support with complete postpartum visits, 26 people (63.4%) p value = 0.03. There is a relationship between mileage, work and family support with complete postpartum visits at the Griya Sehat Clinic in 2021. Midwives are expected to increase counseling and information about midwifery care during the puerperium and breastfeeding, especially postpartum visits.